Exercise, Manual Therapy, and Booster Sessions in Knee Osteoarthritis: Cost-Effectiveness Analysis From a Multicenter Randomized Controlled Trial. Issue 1 (23rd October 2017) - Bove, Allyn M; Smith, Kenneth J; Bise, Christopher G; Fritz, Julie M; Childs, John; Brennan, Gerard P; Abbott, J Haxby; Fitzgerald, G Kelley
Abstract: Background: Limited information exists regarding the cost-effectiveness of rehabilitation strategies for individuals with knee osteoarthritis (OA). Objective: The study objective was to compare the cost-effectiveness of 4 different combinations of exercise, manual therapy, and booster sessions for individuals with knee OA. Design: This economic evaluation involved a cost-effectiveness analysis performed alongside a multicenter randomized controlled trial. Setting: The study took place in Pittsburgh, Pennsylvania; Salt Lake City, Utah; and San Antonio, Texas. Participants: The study participants were 300 individuals taking part in a randomized controlled trial investigating various physical therapy strategies for knee OA. Intervention: Participants were randomized into 4 treatment groups: exercise only (EX), exercise plus booster sessions (EX+B), exercise plus manual therapy (EX+MT), and exercise plus manual therapy and booster sessions (EX+MT+B). Measurements: For the 2-year base case scenario, a Markov model was constructed using the United States societal perspective and a 3% discount rate for costs and quality-adjusted life years (QALYs). Incremental cost-effectiveness ratios were calculated to compare differences in cost per QALY gained among the 4 treatment strategies. Results: In the 2-year analysis, booster strategies (EX+MT+B and EX+B) dominated no-booster strategies, with both lower health care costs and greater effectiveness. EX+MT+B had the lowest total health care costs. EX+B cost $ 1061 more and gained 0.082 more QALYs than EX+MT+B, for an incremental cost-effectiveness ratio of $ 12, 900/QALY gained. Limitations: The small number of total knee arthroplasty surgeries received by individuals in this study made the assessment of whether any particular strategy was more successful at delaying or preventing surgery in individuals with knee OA difficult. Conclusions: Spacing exercise-based physical therapy sessions over 12 months using periodic booster sessions was less costly and more effective over 2 years than strategies not containing booster sessions for individuals with knee OA.